Calvin dan Spiritualitas Kerahiman - Stella Yessy Exlentya Pattipeilohy (GEMA TEOLOGIKA: Jurnal Teologi Kontekstual dan Filsafat Keilahian, 2017)
Abstract The keyword commonly used in mysticism and spirituality is "experience". The instilling of God's mercy, in fact, is a spiritual experience accosted by God's love. Such experience is shared in a transformative praxis. The mercy of God is a faith experience that could be made a meeting point in fostering a love-based religious life. In the Protestant tradition, we can find a foothold for the development of spiritual theology on John Calvin's work, i.e. the so-called merciful spirituality. Today's experience of God's mercy is influenced by the contextual concern abaout the image of the Homeless Jesus. The refugees not only "challenge" Christian communities to recognise the Christ within the needy strangers, but also welcome them in love and peace despite religious faith differences. Abstrak Kata kunci yang umum digunakan dalam dunia mistik atau spiritualitas adalah "pengalaman" (experience). Penghayatan akan kerahiman Allah sesungguhnya adalah pengalaman spiritual disapa oleh cinta kasih Allah. Pengalaman ini berlanjut dalam tindakan mencinta dan dibagikan bagi sesama dalam praksis transformatif. Allah yang merahimi menjadi pengalaman iman yang dapat dijadikan titik temu dalam mengembangkan hidup beragama yang dasarnya adalah cinta kasih. Di dalam tradisi Protestan dapat ditemukan pijakan mengembangkan teologi spiritualitas Protestan, yaitu pada spiritualitas John Calvin yang disebut spiritualitas kerahiman. Pengalaman akan kerahiman Allah di masa kini ditantang oleh keprihatinan kontekstual dalam gambaran Homeless Jesus. Pengungsi tidak hanya "menantang" umat Kristiani untuk mengenali Kristus dalam diri orang asing dan membutuhkan, tetapi juga menyambutnya dalam kasih dan damai sekalipun mereka berbeda agama atau keyakinan.